Compact and low insertion loss UWB on‐chip bandpass filter using coupled meandered line. Issue 6 (14th February 2020) - Jiang, Yan; Tang, Wanchun; Shi, Yongrong; Zhou, Peng; Feng, Linping
Abstract: For ultra‐wideband (UWB) communication applications, a low‐loss compact filter is proposed based on coupled lines using the GaAs integrated passive devices (IPD) technology in this letter. The multistage coupling lines are used to realize the ultra‐wide passband with 100% fractional bandwidth. Two modified stubs loaded with shorted capacitors are introduced between coupled lines to produce a new transmission zero near the lower passband edge, resulting in better frequency selectivity performance. Moreover, stepped impedance resonator (SIR) structure is applied to the coupled lines to improve impedance matching performance within ultra‐wide passband. As demonstrated, the proposed filter is fabricated as a chip with a compact size of 1.8 × 1.7 mm 2, that is, 0.257 × 0.242  λ g 2 . The measured results show that the insertion loss of the filter is less than 1.5 dB from 6 to 18 GHz with the return loss better than 13.5 dB. All simulated and measured frequency responses of the proposed filter are found to match well with each other, which further demonstrates the claimed superior performances of the proposed filter.